MEDICAL STUDENT’S ACADEMIC ACHIEVEMENT BETWEEN FIRST AND SECOND YEAR: A SINGLE-INSTITUTION CASE REPORT - Agus Cahyono; Sasa Sajuni (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2022)
Background: Difficulties in achieving good academic achievement of medical student in early year is a concerning issue. Medical students may experience failure due to many factors. These factors may came from the students (internal) or from environment (external). Self motivation, time to have social media, and watching televition are example of internal factors. Meanwhile method of teaching learning, study environment, and family condition are example of external factors. Aims: To identify factors that influence academic achievement of medical students of Universitas Surabaya (Ubaya). Case discussion: This study used questionnaires to identify factors that influence academic achievement. The study conducted in 90 students. Academic achievement between first and second year was compared. Data was analized using t test comparative mean for significancies with α 0,05. The factors studied were sex, father’s education, mother’s education, duration for study, duration of having social media, duration for team work, duration for hobbies, special relationship with friend, routine supply of living cost, sufficiency of living cost, personal interest to medical faculty, and chose medical faculty as parents’s advice. Among the factors that influence academic achievement of medical students, being a woman and having personal interest to medical faculty were significantly influence academic achievement of medical students of Ubaya. Conclusion: Being a woman and having personal interest to medical faculty were significantly influence academic achievement of medical students of Ubaya.